Education and Exhibition Display Design in Taman Mini Indonesia Indah - Anak Agung Ayu Wulandari; Ulli Aulia Ruki (Bina Nusantara University, 2018)
This research aimed to look further at Taman Mini Indonesia Indah’s (TMII) role in education and to enrich its visitors through exhibition design inside their main attraction, the traditional houses. It used the qualitative methods through observation of three randomly selected pavilions and data analysis used SWOT analysis and goal grid diagram. The research shows that there are no engagements between objects and visitors, the exhibitions are still lack of planning, visually unattractive and unavailability of information or written texts for most of its collection, which can be concluded that TMII is still far from achieving their educational goal. The result of this research is preliminary design for display cases that can be used in pavilions and corresponds design standards.